On Instructional Materials: The Pre-Service Teachers Preferences in Time of Pandemic - Lynn M. Besa; Richard E. Parcon (Basic and Applied Education Research Journal, 2021)
The outbreak of the Covid-19 pandemic did not only surprise many but also caught most of the academic institutions unprepared. As such, the best option to continue the academic year is to go distance education through flexible learning modes. However, several issues are tied to the implementation of the different modes of learning. To find the most appropriate materials in teaching, this study tried to assess the voice of the learners as one of the considerations in the learning system. Using a descriptive method in which the textual responses from 130 English Major Students were converted to quantitative data to establish patterns and qualitative response analysis to capture the implications of the participants’ responses, the researchers analyzed the proposals of the pre-service teachers and their implications to teaching and learning. Findings reveal that the participants implicitly based their preferences on some considerations. Hence, the diversified instructional materials imply their capability and willingness to use various sources and are in favor of engaging in the hybrid form of instructions. Results also indicate that teachers’ preparations should be parallel to the preferences of the learners to meet the demands of the new normal teaching set up.